Tax Bunching at the Kink in the Presence of Low Capacity of Enforcement: Evidence from Uruguay - Marcelo Bergolo; Gabriel Burdín; Mauricio De Rosa; Matias Giaccobasso; Martin Leites (Institute of Labor Economics (IZA), 2019)
By using a bunching design on rich administrative tax records from Uruguay's tax agency we explore how individual taxpayers respond to personal income taxation in a context with high sheltering opportunities. We estimate a moderated elasticity of taxable income in the first kink point (0.16) driven by a combination of gross labor income and deductions responses. Taxpayers use personal deductions more intensively close to the kink point and undereport income unilaterally or through employer-employee collusion. Our results suggest that policy efforts should be directed at broadening the tax base and improving the enforcement capacities rather than eroding tax progressivity.
Keywords: H21; H24; H30; J22; 330; deductions behavior; elasticity of labor income; tax bunching; personal income taxation; misreporting; developing economies